Comparative Analysis and Development of a Flavor Fingerprint for Volatile Compounds of Vegetable Soybean Seeds Based on Headspace-Gas Chromatography-Ion Mobility Spectrometry - Yuan, Fengjie; Fu, Xujun; Yu, Xiaomin; Yang, Qinghua; Jin, Hangxia; Zhu, Longming (Frontiers in Plant Science, 2021)
BACKGROUND: Evaluation of the volatile compounds and found some characteristic fingerprints in vegetable soybean core cultivars would provide useful information and improve aroma in vegetable soybean breeding program. In this study, headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) was used to evaluate the volatile compounds of the stage specific vegetable soybean seeds. RESULTS: In all samples, 93 signal peaks were identified and 63 compounds were qualitative, 14 volatile flavor compounds corresponded to multiple signals. Of the 63 volatile compounds belong to different classes: esters (15), aldehydes (15), alcohols (13), ketones (15), acid (1) and others (4). Peak intensity of most volatile compounds varied greatly among different core cultivars. Alcohols and aldehydes compounds decided the basic volatile flavor of vegetable soybean seeds, special violatile flavor were determined by their respective esters, Ketones or other compositions. Characteristic fingerprints were found in some core vegetable soybean cultivars. Four cultivars had pleasant aroma, because of higher content of 2-AP, they were xiangdou, ZHE1754, Zhexian 65018-33 and qvxian No.1. PCA were employed to distinguish the samples based on the signal intensity of the violate components, the results showed that samples from different ecotype, original area and breeding direction could possess their special volatile compounds which were different from others in term of content. CONCLUSION: The composition and concentration of volatile compounds differs greatly among vegetable core cultivars, the volatile flavor compounds of soybean seeds were determined by their ecotype of cultivars, direction of breeding selection and original area. Some characteristic fingerprints of vegetable cultivars were established by HS-GC-IMS, they could be used to describe and distinguish cultivars and their offsprings in future breeding researches.